Mengatasi Permasalahan Pembelajaran Pendidikan Agama Islam Di Sekolah Umum - Fulan Puspita (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2023)
This paper is background by the existence of Islamic Religious Education teachersin public schools who have a fundamental problem in the implementation ofIslamic Religion education, namely the lack of time to study Islamic Educationsubjects. This then requires the best solution so that the objectives of learning PAIin public schools can be achieved. The research method used is a qualitativelibrary research approach. The results of this paper found that to overcome the lack of PAI study hoursin schools, PAI teachers must innovate learning by using various approaches suchas the faith approach, the habituation approach, and the emotional approach. Allthree must be used to achieve learning objectives and students at school canpractice directly at school